The evaluation of candidates in a personnel selection: Preference for experience over potential in unfavorable contexts - Paredes, Borja; Del Olmo, Samuel; Santos, David; Gandarillas, Beatriz; Briñol, Pablo (Anales de Psicología / Annals of Psychology, 2019)
The present research´s main goal is to examine the evaluation of a job candidate as a function of his profile and the context of the organization. An experiment was conducted with a sample of participants trained in personnel selection. Participants first received a message describing that the future of a given organization was favorable or unfavorable. Then, all participants were asked to read the information about a potential job candidate for such organization. The candidate was described in terms of his previous experience or in terms of his potential as a professional. After receiving the information about the organization and the profile, all participants were asked to evaluate the job candidate. We expected that there would be a higher preference for experience relative to potential, particularly when the context was unfavorable. As predicted, results showed that under unfavorable contextual conditions, attitudes towards the candidate were more favorable when the job candidate was portrayed in terms of experience (vs potential). Under favorable contextual conditions, attitudes towards the candidate did not vary as a function of his profile.